Analisis Ragam Makna Semantik Pada Lagu “Kala Sang Surya Tenggelam” Karya Chrisye - Risma Ayu Destrian; Pemmy Meisya Kumari; Fikri Hakim (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This research aims to reveal the various semantic meanings in the lyrics of the song "Kala Sang Surya Tenggelam" by Crishye. Song lyrics are an indirect means of communication to express the meanings implied therein. Of course, this cannot be separated from semantics which plays a crucial role in revealing the meanings. what is implied and written in song lyrics. Semantics is a science that examines and studies meaning in a language. This research uses a qualitative approach with descriptive research methods. which will be analyzed includes all the words, phrases and sentences in the lyrics of Chrisye's song. The results obtained are various meanings in the lyrics, including (1) lexical meaning consisting of synonyms, antonyms, repetition affixation, reduplication, composition (3) meaning of proverb.